2013
DOI: 10.1074/jbc.m112.449561
|View full text |Cite
|
Sign up to set email alerts
|

Structural Units Important for Activity of a Novel-type Phosphoserine Phosphatase from Hydrogenobacter thermophilus TK-6 Revealed by Crystal Structure Analysis

Abstract: Background: Sequence-based annotation of novel-type phosphoserine phosphatases (iPSPs) is difficult because of their diverse substrate preferences. Results: Crystal structure and mutation analyses of iPSP1 from Hydrogenobacter thermophilus identified the residues involved in substrate recognition. Conclusion: The His85 side chain and C-terminal region of iPSP are important for its phosphoserine phosphatase activity. Significance: These findings will help to identify iPSPs from sequence databases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Under optimum conditions, we found that the K m (52 μM) for l ‐phosphoserine was similar to those of rat brain (68 μM) (Hawkinson et al ., ) and E. coli (97 μM) (Chiba et al ., ), but lower than those of Thermus thermophilus (0.25 mM) (Chiba et al ., ) and Hy. thermophilus (1.6 mM for metal independent PSP1 (iPSP1) and 1.5 mM for metal independent PSP2 (iPSP2)) (Chiba et al ., ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Under optimum conditions, we found that the K m (52 μM) for l ‐phosphoserine was similar to those of rat brain (68 μM) (Hawkinson et al ., ) and E. coli (97 μM) (Chiba et al ., ), but lower than those of Thermus thermophilus (0.25 mM) (Chiba et al ., ) and Hy. thermophilus (1.6 mM for metal independent PSP1 (iPSP1) and 1.5 mM for metal independent PSP2 (iPSP2)) (Chiba et al ., ).…”
Section: Discussionmentioning
confidence: 91%
“…Notably, the PSP of Hy. thermophilus has been reported to be independent of Mg 2+ (Chiba et al ., ). Thus, our findings showed that bmPSAT is not similar to Hy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The Synpcc7942_2078 protein shares structural features with an E. coli PGM control but is nonessential; thus, it was annotated as a PGM performing this regulatory function. Synpcc7942_0485 shares strong structural similarity to a phosphoserine phosphatase (PSP) in Hydrogenobacter thermophiles (24) and has sequence homology to the recently characterized PSP in PCC 6803 (25). Thus this gene was confidently annotated as a PSP in S. elongatus.…”
Section: Resultsmentioning
confidence: 91%
“…A novel type of phosphoserine phosphatase of Hydrogenobacter thermophiles [55] was also identified as the most similar protein with known crystallographic structural data. However, the possible tetrameric structure of Rv2135c in the native form warrants further biochemical, computational and crystallographic studies in order to ascertain the natural substrate of this enzyme.…”
Section: Discussionmentioning
confidence: 99%